Content Marketing Optimization: A/B Testing and Conjoint Analysis for Engagement Strategies in Jordan - Mohammad, Anber Abraheem Shlash; Al- Daoud, Khaleel Ibrahim; Al- Daoud, Suleiman Ibrahim Shelash; Samarah, Tariq Ali; Vasudevan, Asokan; Li, Minmin (Journal of Ecohumanism, 2024)
This study will focus on three most important content marketing attributes: Headline Type, Message Tone, and Visual Design, revolving around user engagement metrics like Click-through Rate (CTR), Conversion Rate, and Bounce Rate. We then extracted data from digital marketing platforms in Jordan and performed a wide range of statistical techniques: ANOVA, conjoint analysis, and Chi-square tests to find the effect of these content features on user behaviour.Key observations indicate that headline types are informal, question-oriented, or statement-natured, these highly increase CTR and conversion but also amplify the chances of bounce rates. Similarly, message tones that are culturally fit or formal see an improvement in CTR and conversion but might lead to an increased rate in bounce rates. Similarly, visual designs.In fact, the study concludes that some of the content attributes actually serve to divert users' attention to increasing conversions while also growing the odds of users bouncing quicker, assuming the content does not meet the expectations created. That exigently underlines the need for a delicate balance between engaging content and value-driven substance. The findings provide direct actionable insights for the content marketers in order to help them optimize their strategies by aligning engaging elements with content that sustains long-term user interaction.